2012
DOI: 10.1074/jbc.m112.344887
|View full text |Cite
|
Sign up to set email alerts
|

The TGFβ Receptor-interacting Protein km23-1/DYNLRB1 Plays an Adaptor Role in TGFβ1 Autoinduction via Its Association with Ras

Abstract: Background:The TGF␤ receptor-interacting protein km23-1 plays an important role in TGF␤ signal transduction in TGF␤-sensitive epithelial cells. Results:The role of km23-1 in TGF␤ activation of Ras/JNK/ERK, as well as TGF␤1 autoinduction, was determined. Conclusion: km23-1 is required for TGF␤1 autoinduction through a Smad2-independent Ras/ERK/JNK pathway. Significance: km23-1 functions as a critical adaptor coupling TGF␤ receptors to Ras activation after TGF␤ treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 59 publications
2
17
1
Order By: Relevance
“…The pRNATin-H1.2/hygro km23-1 siRNA and the relevant NC siRNA sequences have been described previously [34], [36]. Further, we have developed RKO cell clones (#1, #5) stably expressing km23-1-specific siRNA and confirmed km23-1 depletion by Western blot analysis of protein lysates isolated from the stable transfectants as described previously [35]. We further confirmed the efficiency of km23-1 silencing in RKO cells at the mRNA level.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…The pRNATin-H1.2/hygro km23-1 siRNA and the relevant NC siRNA sequences have been described previously [34], [36]. Further, we have developed RKO cell clones (#1, #5) stably expressing km23-1-specific siRNA and confirmed km23-1 depletion by Western blot analysis of protein lysates isolated from the stable transfectants as described previously [35]. We further confirmed the efficiency of km23-1 silencing in RKO cells at the mRNA level.…”
Section: Resultssupporting
confidence: 69%
“…These pRNATin-H1.2/hygro siRNA vectors were transfected into RKO cells using Lipofectamine 2000 (Invitrogen) according to the manufacturer's protocol. The empty vector (EV), NC siRNA, and km23-1 siRNA (km23-1 siRNA clone #1 and clone #5) RKO stable transfectants were prepared, characterized, and routinely maintained in growth medium with 100 µg/ml of hygromycin B as described previously [35].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, we have shown that Ras and km23-1 form a TGFβ-regulated complex in vivo [17]. However, km23-1 is actually part of an ancient superfamily, widely represented in archaea and bacteria, which appears to be involved in regulating NTPase activity [18].…”
Section: Introductionmentioning
confidence: 99%